Cytological Effects of Irradiated Guayabano Fruit Juice on Native Onion ( Allium fistulosum L.) - Serrana, Milagros; Arañez, Adoracion (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Thirty bottles of guayabano fruit juice were exposed to gamma ray doses of 0, 1, 2, 3 and 4 KGy. These bottles were then stored for 0, 4 and 8 days and used for treatment of Allium fistulosum L. root meristems. For each treatment, 2000 cells were scored to obtain data on mitotic index and types and frequency of cytological aberrations. The newly irradiated juice did not inhibit mitosis but storage showed marked effects on the mitotic index. Both irradiated or unirradiated juice stored for 8 days caused a significant inhibition of mitosis. The irradiated juice induced the production of anaphase bridges, binucleate cells, cells, cells with elongated nucleus and cells with obliquely oriented equatorial plate.